Insecurity and Economic Growth in Nigeria: A Diagnostic Review - Onime, Bright Enakhe (European Scientific Journal, ESJ, 2018)
This paper examines the effect of insecurity on economic growth in Nigeria. Apart from its direct effect on the populace, it also affects the economy. Using elements of descriptive qualitative analysis and data from secondary sources, the paper analyzed its effect on some economic parameters. The analysis showed that insecurity affects economic growth by drying-out investments, increases unemployment and dwindles government revenue, amongst others. Despite these effects, government capital expenditure on internal security did not grow astronomically to match the hydra-headed problem. This paper therefore recommended an increase in capital expenditure on internal security and concludes with a discussion of some policies to be designed and targeted at addressing the economic effects of insecurity.